Refleksi Nilai-nilai Budaya Lokal Di Balik Praktik Akuntansi Masjid - Thalib, Mohamad Anwar; Suhega, Hilwa Faradhilla; Huruji, Sindriyanti (Journal of Islamic Philanthropy and Disaster (JOIPAD), 2023)
Abstract: This study aims to photograph mosque cost accounting based on local wisdom values in Gorontalo. This research topic is important to do because it is an effort to preserve local cultural values from cost accounting practices. This study uses an Islamic paradigm with an Islamic ethnomethodological approach. There are five data analysis stages: charity, knowledge, faith, revelation information, and good deeds. The results showed that the salaries of the worshiper prayer, preacher, caller prayer, and cleaners were taken from the mosque's charity box. The cost of constructing the mosque was obtained from donations from the community, both in the form of building materials and money. In contrast, the cost of providing equipment was taken from the personal funds of the mosque management. The practice of cost accounting is conditional on the value of gratitude (sukuru) and sincerity (ihilasi), which manifest faith in the Creator. In the culture of the people of Gorontalo, these values are often instilled by parents through lumadu "diila o'onto, bo wolu-woluwo" which means invisible but there. This phrase teaches that in life, do not just chase what is visible but also look for something that is not visible but exists.Keywords; cost, mosque, Islamic ethnomethodology, Gorontalo Abstrak. Penelitian ini bertujuan untuk memotret akuntansi biaya masjid berbasis nilai-nilai kearifan lokal di Gorontalo. Topik penelitian ini penting untuk dilakukan karena sebagai upaya untuk melestarikan nilai-nilai budaya lokal dari praktik akuntansi biaya. Penelitian ini menggunakan paradigma Islam dengan pendekatan etnometodologi Islam. Terdapat lima tahapan analisis data yaitu amal, ilmu, iman, informasi wahyu, dan ihsan. Hasil penelitian. Biaya gaji imam, khotib, adzan, dan petugas kebersihan diambil dari kotak amal masjid. Biaya pembangunan masjid diperoleh dari sumbangan masyarakat baik dalam bentuk bahan bangunan maupun uang, sementara itu biaya penyediaan peralatan diambil dari dana pribadi pengurus masjid. Praktik akuntansi biaya tersebut syarat dengan nilai syukur (sukuru) dan ikhlas (ihilasi) yang merupakan wujud dari iman kepada Sang Pencipta. Dalam kebudayaan masyarakat Gorontalo nilai-nilai tersebut sering ditanamkan oleh para orang tua melalui lumadu “diila o’onto, bo wolu-woluwo” artinya tidak kelihatan tetapi ada. Makna ungkapan ini adalah mengajarkan bahwa dalam kehidupan, jangan hanya mengejar yang kelihatan, tetapi juga mencari sesuatu yang tidak kelihatan tetapi sebenarnya ada. Kata kunci; biaya, masjid, etnometodologi Islam, Gorontalo